CHANGES IN THE PROPERTIES OF MOUNTAIN FOREST SOILS IN THE ZONE OF MIXED BEECH FORESTS OF THE UKRAINIAN CARPATHIANS UNDER THE INFLUENCE OF WATER EROSION - Korinets Ю.; Khirivskyi П.; Zelisko О.; Krektun Б. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
The study investigates erosion of mountain forest soils and its dependence on a number of factors of natural and anthropogenic origin, establishes the type and character of erosion processes in connection with logging and the properties of brown forest soils of the Carpathians, and determines the sizes and volumes of soil losses as a result of erosion. The data on the various nature of the influence of the steepness of the slope on the dynamics of erosion processes are given, and the value of removal by the intrasoil runoff of fine soil is determined. The brown forest soils in the indicated forest cuts differ in the content of the skeleton. An increase in the skeletal structure of brown forest soils in conditions of a mild, humid climate does not cause a noticeable deterioration of their forest vegetation conditions. The mechanical composition and especially the skeletal structure affect the physical properties and determine the relationship of the soil to erosion processes. The increase in the intensity of erosion from top to bottom is caused by an increase in the strength of the flow due to the inflow of water from the upper elements of the relief. Shallower poorly developed light brown forest soils are less resistant to the development of erosion processes compared to deeper dark ones. On less stony soils in the lower part of the slope, after the felling of the forest, a slight decrease in porosity and a sharper decrease in the infiltration capacity of the upper horizon were noted. On heavily stony soils, after the felling of the forest, fine soil and the most important nutrients were washed away from the upper horizons of the soil. Significant losses cause a sharp decrease in forest plant properties of skeletal soils, and sometimes turn them into stony placers unsuitable for reforestation. The erosion of mountain forest soils caused by predatory management is described. As a result of the research, production organizations will receive recommendations for the widespread implementation of erosion control measures.